The Effect of Environmental Performance, Leverage and Company Size Towards Carbon Emission Disclosure on Rated Proper Company in 2015-2018 - Indra Widianto; Dian Purnama Sari (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2020)
Abstract: Carbon emission disclosure is a form of communication that is important and necessary to fulfil the needs and interests of information to the company’s stakeholders. That statement is caused by stakeholder theory, when the company conducts its operational company can’t focus on company purposes or interests only, but company must pay attention to the stakeholder’s interests and provide benefits for stakeholder which can be done by disclosing financial and non-financial information included carbon emission disclosure as a form of corporate responsibility to stakeholders. The purpose of this research is to analyze and provide empirical evidence about the effect of environmental performance, leverage and company size against carbon emission disclosure on rated PROPER company in 2015-2018. This research is a form of quantitative research with hypothesis testing. Technique used for data analysis is multiple linear regression. The results of this research explained that environmental performance and company size has positive and significant effect on carbon emission disclosure. On the other hand, leverage has no effect on carbon emission disclosure. Keywords: carbon emission disclosure, environmental performance, leverage, company size.